2014
DOI: 10.1371/journal.pone.0090129
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinoschisis in Glaucomatous Eyes

Abstract: PurposeTo investigate the structural and clinical characteristics of peripapillary retinoschisis observed in glaucomatous eyes using spectral-domain optical coherence tomography (SD-OCT).MethodsCircumpapillary retinal nerve fiber layer (cpRNFL) and macular cross-hair SD-OCT scans and infrared fundus images of the glaucoma patients from the Investigating Glaucoma Progression Study (IGPS) and healthy volunteers were reviewed. Optic disc images obtained using enhanced depth imaging (EDI) SD-OCT were also evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 35 publications
9
78
0
Order By: Relevance
“…It showed subtle dehiscence at the nerve fiber layer in sectional OCT scans, but the affected area was dramatically larger than expected from an en face view. Recent studies showed that peripapillary retinoschisis was occasionally detected in glaucomatous eyes, [21][22][23] but all our subjects denied history of glaucoma. Intraocular pressure and perimetry test were within normal range.…”
Section: Discussionmentioning
confidence: 56%
“…It showed subtle dehiscence at the nerve fiber layer in sectional OCT scans, but the affected area was dramatically larger than expected from an en face view. Recent studies showed that peripapillary retinoschisis was occasionally detected in glaucomatous eyes, [21][22][23] but all our subjects denied history of glaucoma. Intraocular pressure and perimetry test were within normal range.…”
Section: Discussionmentioning
confidence: 56%
“…More recently, two different studies with larger samples of peripapillary retinoschisis in glaucomatous eyes have been published [ 15 , 16 ]. One study was about the structural and clinical characteristics [ 15 ] and the other was about the effect of retinoschisis on RNFL thickness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [20] evaluated by HD-OCT imaging 22 cases of peripapillary retinoschisis without a serous detachment in glaucomatous eyes. The resolution of the retinoschisis during follow-up was associated with an IOP reduction.…”
Section: Discussionmentioning
confidence: 99%